PROPERTY INSURANCE AND INNOVATIVE BUILDING TECHNIQUES - REDUCING THE CONSEQUENCES OF CLIMATE CHANGE - Milinković, Ozrislava; Brzaković, Pavle; Milošević, Olgica; Brzaković, Miodrag (Economics of Agriculture, 2020)
Climate changes are recognized as a matter of global importance. They can have a long term monetary and nonmonetary influence on the lives and prosperity of people. Almost all industries are affected by climate change, but insurance companies and the construction industry suffer particularly high pressure. Due to the unpredictability of climate changes and increased risk, the possibility of withdrawing insurance against natural disasters has been considered. From the construction industry, it is required to adapt to changes, by building less polluting buildings, resistant to destructive effects of climate changes. The insurance industry has recognized the direct connection between green - sustainable practices and reduced risk, which in recent years has been the reason, for becoming a leader in creating, energy and resource efficiency. The contribution of this paper is in the demonstration how innovative construction solution can contribute to sustainable insurance and reducing the consequences of climate change.